Роздуми над апеляційністю слоганів президентської виборчої кампанії 2019, або як «зробити» виборця - Скаб, Мар’ян (My University, 2020)
The article is devoted to the analysis of the appellate component of slogans from election campaign billboards in the presidential campaign of 2019. Virtually every slogan contains components that explicitly and implicitly mark the semantics of appeal, and language forms, used to convey subject meaning, are primarily vocative forms of nouns; and to transmit predicate meaning - imperative forms and constructions and their functional equivalents are used. The peculiarity of political advertising is the presence of the widest and most general addressee, which allows the creators of slogans not to use vocatives to enote the voter, and, consequently, the appeal of a campaign focuses almost exclusively on the direct or covert expression of its predicate component. The slogans of the presidential election campaign 2019 are classified by communication and it is proved that the appeal is most clearly represented by slogans-calls; and slogans-messages and slogans-promises (including slogans-threats) contain it in a hidden form (it is worth to note that candidates started campaigns with slogans-messages and resorted to slogans-imperatives only in the following stages). Indirect information about those, whom the slogan is directed to, is expressed by the content of the part of it, which presents a universal advertising offer, by features of language tools and ways of design of the slogan in general. The unique advertising proposal in the analysed slogans is a call to elect a President with certain qualities, especially moral, to draw attention to the uniqueness of a candidate, to promote change (real or imagined), to promise to acquire specific social or material values.The analysis of slogans from the point of view of their normativity, their efficiency, forecasted and real, is carried out.
Reflections on the appeals in the slogans of the presidential election campaign 2019, or how to "zrobyty vybortsia"
Keywords: political advertising; an appellate component of the slogan; slogan-call; slogan-message; slogan-promise; slogan-threat